2009
DOI: 10.1093/geront/gnp099
|View full text |Cite
|
Sign up to set email alerts
|

Caregiver Mental Health and Potentially Harmful Caregiving Behavior: The Central Role of Caregiver Anger

Abstract: Identifying anger levels among caregivers who report symptoms of depression is warranted. Reducing depression in caregivers who report high levels of anger may result in reductions of PHB. Screening for resentment is warranted, as the relation between resentment and anger is similar to that between depression and anger.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
81
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(88 citation statements)
references
References 41 publications
4
81
0
2
Order By: Relevance
“…Previous studies identified four main forms of elder abuse including physical abuse which refers to any conduct that violates the physical integrity of an older person; sexual abuse which is the conduct that violates the sexual integrity of an older person; and psychological abuse which refers to any form of degrading or humiliating conduct such as instilling fear, name calling and isolation of an older person (MacNeil et al 2010. Other forms of elder abuse are economic or financial abuse which refers to the illegal taking, misuse, or concealment of funds, property or assets or intentional and unintentional abandonment or denial of support to an older person by people expected to provide such support (Mudiare 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Previous studies identified four main forms of elder abuse including physical abuse which refers to any conduct that violates the physical integrity of an older person; sexual abuse which is the conduct that violates the sexual integrity of an older person; and psychological abuse which refers to any form of degrading or humiliating conduct such as instilling fear, name calling and isolation of an older person (MacNeil et al 2010. Other forms of elder abuse are economic or financial abuse which refers to the illegal taking, misuse, or concealment of funds, property or assets or intentional and unintentional abandonment or denial of support to an older person by people expected to provide such support (Mudiare 2013).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Caregivers' reduced perceived selfefficacy results in reduced functional abilities of people with dementia (Ablitt, Jones, & Muers, 2009). Caregivers feeling stress and experiencing mental health problems are at risk for engaging in abusive acts against older care recipients (Macneil et al, 2010). Although caregiver health status is significantly influenced by where the person with AD resides, total burden does not significantly differ between caregivers of community-dwelling patients and caregivers of institutionalized patients (Fredman et al, 2008).…”
Section: Background Literaturementioning
confidence: 99%
“…In chronic illnesses sometimes caregivers adopt humiliating attitude towards care recipient and show disrespect, get them insulted, commit offenses against them, ridicule them, sometimes even they underestimate their potentials and show teasing behaviors to the patients. 15 Anger was a prevailing factor between potentially harmful behavior and anxiety. Moreover depression was significantly associated with subjective burden and anxiety as compared to objective burden while anger was inversely related to the mental health.…”
Section: Introductionmentioning
confidence: 99%